2011
DOI: 10.1103/physreve.83.031306
|View full text |Cite
|
Sign up to set email alerts
|

Shallow granular flows

Abstract: Many processes in geophysical and industrial settings involve the flow of granular materials down a slope. In order to investigate the granular dynamics, we report a series of laboratory experiments conducted by releasing grains at a steady rate from a localized source on a rough inclined plane. Different types of dense granular flow are observed by varying the flow rate at the source and the slope of the inclined plane. The two cases of steady flow confined by levees and the flow of avalanches down the plane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
94
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(106 citation statements)
references
References 38 publications
11
94
1
Order By: Relevance
“…Although this approximation is crude, in that it does not explicitly resolve the basal entrainment or deposition, Edwards & Gray (2015) showed that it was able to predict accurately the amplitude, wavelength and coarsening dynamics of erosion-deposition waves that spontaneously form in a long channel from a continuous inflow. They observed that typical waves had a ratio of peak height to static layer depth of 2.6 and a typical mobile wavelength of 59 cm, which are both very similar to the waves observed by Takagi, McElwaine & Huppert (2011) in their low-inflow-rate experiments.…”
Section: Introductionsupporting
confidence: 66%
“…Although this approximation is crude, in that it does not explicitly resolve the basal entrainment or deposition, Edwards & Gray (2015) showed that it was able to predict accurately the amplitude, wavelength and coarsening dynamics of erosion-deposition waves that spontaneously form in a long channel from a continuous inflow. They observed that typical waves had a ratio of peak height to static layer depth of 2.6 and a typical mobile wavelength of 59 cm, which are both very similar to the waves observed by Takagi, McElwaine & Huppert (2011) in their low-inflow-rate experiments.…”
Section: Introductionsupporting
confidence: 66%
“…All the results in this paper were performed on a slope of 32 • to the horizontal which is just above the minimum angle for steady flow. At higher angles steady flows were hard to achieve because roll waves develop while at lower angles discrete avalanches occur at lower mass flow rates [3]. The flows in the experiments could be maintained indefinitely by transferring the grains that flowed off The thickness and surface velocity of the flows were measured 2 m down the slope where the flows were steady and no longer depended on the x position.…”
Section: Laboratory Experimentsmentioning
confidence: 99%
“…When a granular material is released steadily from a localised source down a rough plane inclined at a range of angles, a steady flow develops between static levées down the slope [1][2][3]. Remarkably, however, the surface of the flowing region is not parallel to the inclined plane, but is curved across the slope with the height decreasing from the middle toward the levées.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations